The promising combination therapy strategy for overcoming resistance to histone deacetylase inhibitors in diffuse large B‐cell lymphoma - Haixiang Pei; Yihua Chen (Wiley, 2022)
Abstract Single histone deacetylases inhibitors (HDACis) or current combination therapies show limited clinical efficiency in facing the striking heterogeneity of diffuse large B‐cell lymphoma (DLBCL). This commentary reviews the research conducted by Wang et al. to demonstrate the mechanism of the highly efficient HDACi LAQ824 and a promising HDCAi‐based combination therapy approach in DLBCL.